Clinical Heterogeneity in Two Siblings Harbouring a Heterozygous PRPH2 Pathogenic Variant - Sanlialp, Ayse; Escher, Pascal; Schaller, André; Todorova, Margarita (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose The aim of the study was to describe the clinical and genetic correlation of a c.469 G>A p.(Asp157Asn) heterozygous pathogenic variant in PRPH2 in two siblings of Italian origin.Patients and Methods Both patients underwent ophthalmic examination, electrophysiological testing, autofluorescence imaging, and optical coherence tomography (OCT). Screening for pathogenic variants of the obtained DNA from the family members was carried out.Results The 52-year-old (♀, index patient) and 50-year-old (♂) siblings had BCVA (OD and OS) of 20/20 and 20/16 (♀) and 20/25 and 20/40 (♂), respectively, and suffered increased sensitivity to glare. Yellow irregular macular deposits, numerous small irregular hypo- and hyperreflective spots at the posterior pole, a patchy loss of photoreceptors, and retinal pigment epithelium (RPE) in the perifoveal region were seen. Electrophysiology showed dysfunction of rods and cones, with more affected cone dysfunction in the index patient, contrary to the generalised rod dysfunction in the brother of the index patient. The clinical, electrophysiological, and multimodal imaging findings of both siblings pointed towards Stargardt retinopathy with heterogenic presentation. The DNA analysis identified an autosomal dominant c.469 G>A p.(Asp157Asn) heterozygous pathogenic variant in PRPH2 associated with autosomal dominant cone-rod dystrophy and rod-cone dystrophy. PRPH2 codes for peripherin-2, a membrane protein that consists of 346 amino acids.Conclusions Our findings confirm a heterogeneity in clinical presentation associated with pathogenic variants in PRPH2. It may follow either an autosomal dominant or an autosomal recessive mode of inheritance and show a very heterogeneous clinical manifestation of retinal degeneration, e.g., autosomal dominant retinitis pigmentosa (♂ sibling; II-3) and autosomal dominant cone-rod dystrophy (index ♀ sibling; II-2), autosomal dominant macular dystrophy, and also autosomal recessive retinitis pigmentosa.
Keywords: PRPH2 mutation; inherited retinal degeneration; cone-rod dystrophy; rod-cone dystrophy; Stargardt retinopathy